Možnosti uporabe lesa v dodajalnih tehnologijah (3D-tiskanju) - Kariž, Mirko (Les (Ljubljana), 2017)
Additive manufacturing technologies have developed greatly over the last decade in terms of technology and printing materials. Special emphasis is placed on the development of cheaper materials that are derived from natural sources, without the release of harmful substances during the manufacturing process, with the possibility of using waste materials and recycling after service life. Wood or wood residues are among the potential raw materials that could be used for 3D printing in combinations with natural and synthetic polymers. It is anticipated that, with the development of additive technologies, the use of wood will also expand to the area of structural elements, such as in the construction of prefabricated houses. A review of publications on the topic of 3D printing with natural raw materials with an emphasis on wood biomass and technologies, where the use of wood particles is possible, was made
Keywords: 3D-tiskanje; additive technology; dodajalne tehnologije; les; lesni ostanki; lesno-plastični kompoziti; wood; wood residues; wood-plastic composites